PROVERBS IN HERODOTUS' DIALOGUE BETWEEN SOLON AND CROESUS (1.30‐33): METHODOLOGY AND 'MAKING SENSE' IN THE STUDY OF GREEK RELIGION. (December 2015) - ELLIS, B. ANTHONY
Abstract : Summary: Several influential scholars have recently argued that Herodotus' thought about the gods and historical causation is inconsistent and 'proverbial' in nature, and these conclusions have been used to support far‐reachingtheories about the nature of ancient Greek religion and archaic thought. Taking the Croesus logos as a case study, I question some of the philosophical premises and methodological practices employed in recent arguments for Herodotus' inconsistency. I argue that much analysis is based on a reductive treatment of key words or phrases (often classed as 'proverbs') in isolation from their immediate context. I also argue that stronger claims about the difference between ancient religious/proverbial thought and modern, secular thought rely on circular reasoning. Finally I explore alternative approaches to the interpretation of the theology of Herodotus' Croesus logos, discussing examples from humanist apologetics to literary analysis in the twenty‐firstcentury. In exploring various approaches to Herodotean exegesis I offer a new analysis of several key concepts (divine nemesis, divine phthonos, sumphorē ) and reassess the dynamics of the dialogue between Solon and Croesus.